Early Predictors for Infectious Complications in Patients With Spontaneous Intracerebral Hemorrhage and Their Impact on Outcome - Lindner, Anna; Kofler, Mario; Rass, Verena; Ianosi, Bogdan; Gaasch, Max; Schiefecker, Alois J.; Beer, Ronny; Loveys, Sebastian; Rhomberg, Paul; Pfausler, Bettina; Thomé, Claudius; Schmutzhard, Erich; et al. (Frontiers in Neurology, 2019)
Background: Infectious complications (IC) commonly occur in patients with intracerebral hemorrhage (ICH) and are associated with increased length of hospitalization (LOS) and poor long-term outcome. Little is known about early ICH-related predictors for the development of IC to allow appropriate allocation of resources and timely initiation of preventive measures. Methods: We prospectively enrolled 229 consecutive patients with non-traumatic ICH admitted to the neurocritical care (NICU) of a tertiary care hospital. Patients were screened daily for IC. Multivariable regression models using generalized linear models were used to identify associated factors with the occurrence of IC and to study the impact of IC on functional outcome, which was assessed using the modified Rankin Scale Score (mRS) after 3 months Unfavorable outcome was defined as mRS ≥3. Results: The most common IC were pneumonia (n=64, 28%) and urinary tract infection (n=54, 24%), followed by sepsis (n=9, 4%) and ventriculitis (n=4, 2%). Patients with higher admission ICH Score (>2) had a higher odd to develop any IC during NICU stay (OR=1.7, 95% CI 1.2-2.3, p=0.02). Moreover, early-onset pneumonia (≤48 hours after admission) was predictive of sepsis occurring at a later time-point (median at day 11 [IQR=6-34 days], adjOR=22.5, 95% CI 4.88-103.6, p<0.001). Having at least one IC and pneumonia itself were independently associated with unfavorable 3-months outcome (adjOR=3.0, 95% CI 1.41-6.54, p=0.005; adjOR=4.2, 95% CI 1.33-13.19, p=0.015, respectively). All patients with sepsis died or had poor functional outcome. Conclusions: Infectious complications are common in ICH patients and independently associated with unfavorable outcome. An ICH Score >2 on admission and early pneumonia may help to early identify patients at high risk of IC to allocate resources and start careful surveillance.